Is a public prosecutor’s investigation more effective than a judicial investigation? - Brkić, Snežana S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
This paper is the result of a mini empirical research on the duration of judicial and public prosecutorial investigations before the High Court in Novi Sad. A total of 100 cases were analyzed, of which 50 cases from 2008 and 50 cases from 2015 and 2016. The first 50 cases were conducted during the validity of the Criminal Procedure code from 2001, while the other 50 cases were conducted during the validity of the Criminal Procedure Code from 2011. In order for the result to be as comparable as possible, we tried to have the same structure of criminal acts represented in both groupes. The author came to the conclusion that a prosecutorial investigation is not faster than a judicial investigation. The search for the suspect, the search for the injured party, the impediment of the lawer, the strike of the lawers, the preoccupation of the public prosecutor, etc. contributed to the somewhat longer duration of the public prosecutorial investigation.